Pengaruh Spiritual Emotional Freedom Technique (SEFT) terhadap Tingkat Nyeri pada Pasien Post Operasi Sectio Caesarea di Ruang Nifas RSUI Harapan Anda Tegal - Nisa Hanifah; Tutik Rahayu; Apriliani Yulianti Wuriningsih (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Caesarean section delivery has side effects such as severe pain at the surgical site. Therefore, a combination of non-pharmacological and pharmacological treatments is needed to reduce the patient's pain perception and shorten the recovery period. Spiritual Emotional Freedom Technique (SEFT) therapy, as a non-pharmacological approach, offers benefits in pain management. The purpose of this study was to determine the effect of Spiritual Emotional Freedom Technique (SEFT) on pain in post-cesarean section patients in the postpartum ward of Harapan Anda Hospital, Tegal City. This study used a quasi-experimental design with a one-group pretest-posttest design. The sample consisted of 53 post-cesarean section patients using a non-random sampling technique. The instruments used were the Numeric Rating Scale (NRS), Standard Operating Procedures (SOP), and observation sheets. Data analysis used Wilxocon. The characteristics of 53 post-Cesarean section patients were mostly elderly aged 20-35 years (62.3%), some with high school education (54.7%), with unemployed status (60.4%), with gravida multigravida status (66%), and with a history of cesarean delivery (52.8%). Before the application of the Spiritual Emotional Freedom Technique (SEFT), most experienced moderate pain levels (49.1%), and after the application of the Spiritual Emotional Freedom Technique (SEFT), most experienced mild pain levels (47.2%). There is an effect of the Spiritual Emotional Freedom Technique (SEFT) on pain in post-Cesarean section patients in the Postpartum Ward of RSUI Harapan Anda, Tegal City (0.000).